Dealing with difficult people - Lenz, Mike; McCormick, Eleanor (HBR emotional intelligence series., 2022)
Learn how to deal with difficult colleagues and clients. At the heart of dealing with difficult people is handling their-and your own-emotions. How do you stay calm in a tough conversation? How do you stay unruffled in the face of passive-aggressive comments? And how do you know if you're difficult to work with? This book explains the research behind our emotional response to awful colleagues and shows how to build the empathy and resilience to make those relationships more productive. Books in this series are based on the work of experts including Daniel Goleman, Tony Schwartz, Nick Morgan, and Daniel Gilbert. This collection of articles includes "To Resolve a Conflict, First Decide: Is It Hot or Cold?" by Mark Gerzon; "Taking the Stress Out of Stressful Conversations," by Holly Weeks; "The Secret to Dealing with Difficult People: It's About You," by Tony Schwartz; "How to Deal with a Mean Colleague," by Amy Gallo; "How To Deal with a Passive-Aggressive Colleague," by Amy Gallo; "How to Work with Someone Who's Always Stressed Out," by Rebecca Knight; "How to Manage Someone Who Thinks Everything Is Urgent," by Liz Kislik; and "Do You Hate Your Boss?" by Manfred F.R. Kets de Vries